Downregulation of CD4+LAP+ and CD4+CD25+ Regulatory T Cells in Acute Coronary Syndromes. (10th December 2013) - Lin, Ying-zhong; Lu, Shan-he; Lu, Zheng-de; Huang, Ying; Shi, Ying; Liu, Ling; Wang, Xiao-yan; Ji, Qing-wei
Abstract : Background . Regulatory T (Treg) cells play a protective role in atherosclerosis prone models and are related to the onset of acute coronary syndromes (ACS, including non-ST-elevation ACS (NSTEACS) and ST-elevation acute myocardial infarction (STEAMI)). CD4+LAP+ Treg cells are a novel subset of Tregs that have been found to ameliorate atherosclerosis in ApoE - / - mice, and these cells also exist in humans. The present study was designed to investigate whether CD4+LAP+ Treg cells are involved in the onset of ACS. Methods . The frequencies of CD4+LAP+ and CD4+CD25+ Treg cells were detected using flow cytometric analysis, and the plasma IL-10 and TGF- β 1 levels were measured using an ELISA in 29 stable angina (SA) patients, 30 NSTEACS patients, 27 STEAMI patients, and a control group (30 cases). Results . The results revealed a significant decrease in the frequencies of CD4+LAP+ and CD4+CD25+ Treg cells and in the levels of IL-10 and TGF- β 1 in patients with ACS compared with those in the SA and control groups. Conclusions . The decrease in the frequencies of CD4+LAP+ and CD4+CD25+ Treg cells may play a role in the onset of ACS.